(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status and identify factors associated with palliative care needs among patients with lung cancer and gastrointestinal cancer treated at Nghe An Oncology Hospital in 2026. Subjects and methods: A cross-sectional descriptive study was conducted on 278 inpatients with lung cancer and gastrointestinal cancer from October 2025 to May 2026. Study using the short form problems and needs in palliative care. Results: The proportion of patients with palliative care needs was 64.7%. The three domains with the highest support needs were physical support (81.3%), assistance with activities of daily living (69.8%), and psychological/spiritual support (62.6%). Factors significantly associated with palliative care needs included educational level above high school (p < 0.05; aOR = 1.92; 95% CI: 1.05-3.50), having family caregivers (p < 0.05; aOR = 3.47; 95% CI: 1.40-8.56), gastrointestinal cancer (p < 0.05; aOR = 2.49; 95% CI: 1.33-4.65), multimodal treatment (p < 0.05; aOR = 5.67; 95% CI: 2.22-14.46), and hospital stay longer than 7 days (p < 0.05; aOR = 2.19; 95% CI: 1.25-3.46). Conclusion: Palliative care needs among patients with lung and gastrointestinal cancers were high, particularly in the physical, activities of daily living, and psychological/spiritual domains. Comprehensive palliative care screening and interventions should be strengthened, with priority given to patients presenting the identified associated factors.